ACCA Paper P2: Corporate Reporting (International and UK Stream) Study Text - BPP Learning Media Ltd (BPP Learning Media Ltd, 2007)
The ACCA Study Text provides the only study material for Paper 2 Corporate Reporting (International and UK Stream) which has been comprehensively reviewed by the Examiner. This unique review guarantees approriate depth and breadth of content and comprehensive syllabus coverage.
Keywords: Accounting; Corporate Reporting; Non-Fiction; Study Text